Identificação e caracterização do aglomerado industrial ervateiro do Alto Vale do Taquari, RS - Greff, Henrique Pinton (2016)
Known scientifically by Ilex paraguariensis, yerba mate, achieved significant economic and social importance, especially in southern Brazil. Considering the region of Alto Vale do Taquari (Polo 4 yerbatero sector), there is the greatest amount of yerba mate produced from the Rio Grande do Sul state, as well as the most yerbateras. The high density oriented industries for the same product in a geographically defined region, and agents that may interact with each other, suggests some characteristics of known organizations such as clusters. The cluster showed a significant industrial concentration in relation to the territory of Rio Grande do Sul, with a QL> 1, where 17.8, the region is considered specialized in yerbatero sector. Moreover, as the indicators used (QL, P (%) and number of establishments), the cluster is considered a development vector location. According to the typology used for characterization of it, the cluster is considered like "Informal", showing the following characteristics: made of micro and small enterprises; Low existence of leadership; small innovative capacity; low domestic confidence; low technological level; little cooperation; high level of competition; lack of new products and export irrelevant. However, it is undeniable the potential that the product yerba mate is, as well as the potential of the Alto Vale do Taquari region with yerbatero sector, but the crowded situation still demands many actions and participation of all agents achieve the full desired development.